2023
DOI: 10.1155/2023/5212712
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Applying Blockchain Technology in Network Public Opinion Risk Management System in Big Data Environment

Abstract: Network public opinion represents public social opinion to a certain extent and has an important impact on formulating national policies and judgment. Therefore, China and other countries attach great importance to the study of online public opinion. However, the current researches lack the combination of theory and practical cases and lack the intersection of social and natural sciences. This work aims to overcome the technical defects of traditional management systems, break through the difficulties and pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Blockchain technology solves many of the privacy, security and credit problems of the digital economy. [4] With the help of blockchain technology in the future, we will be able to quickly realize three-minute loan applications, one-minute e-prescriptions, and one-second invoicing, which will greatly promote the transformation of the digital economy.…”
Section: 2blockchain Triggers a New Round Of Digital Economic Changementioning
confidence: 99%
“…Blockchain technology solves many of the privacy, security and credit problems of the digital economy. [4] With the help of blockchain technology in the future, we will be able to quickly realize three-minute loan applications, one-minute e-prescriptions, and one-second invoicing, which will greatly promote the transformation of the digital economy.…”
Section: 2blockchain Triggers a New Round Of Digital Economic Changementioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%